WORD FORMATION PROCESS OF REGISTER IN PROSTITUTE COMMUNITY FOUND IN MOMMAR EMKA’S “JAKARTA UNDER COVER SEX IN THE CITY” - PRADANA, YOGI ALFRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: word formation processes, register, prostitute community, Jakartaundercover sex in the city.Humans use language as a tool to interface the communication among humans. In the development stages,the language has several variations that occur in certain conditions and opportunities. Register is included in language variations that occur due to the type of employment and particular social class. Registers can be found in the writings form such as books, literature works or in such unwritten form such as general discussion and conversation. On this occasion,the writer is interested in analyzing word formation process of register in prostitute community found in Moammar Emka’s book entitled Jakarta undercover sex in the city. There are three problems to be solved in this study, namely (1) what are the registers found in the prostitution community in Jakarta undercover sex in the city? (2) what are the registers formed by word formation process found in Jakarta undercover sex in the city? (3) what are the meanings of the registers of prostitute community found in Jakarta undercover sex in the city?This study uses qualitative approach to describe the register in prostitute community. Document analysis applied in this study since the data are in the text formin Jakarta undercover sex in the city book.There are 24 chapters to be analyzed. All the data are found in 37 conversations, sentences, or citations in Indonesian. 37 registers found in this study are analyzed using the theory of English word formation process and the theory of Bahasa Indonesia word formation process. There are 15 registers found that are analyzed using English word formation process theory, meanwhile there are 41 registers found that are analyzed using Bahasa Indonesia word formation process theory.The writer suggests the next writer investigate register in prostitute communit y in Emka’s other literally work. The writer also suggests other writer conduct a study which is investigating register in other field besides prostitute community.